(untitled) (The Conference Hub, 2025)
The article is devoted to the methodology for the identification, assessment and development of educational abilities of students. It analyzes methodological approaches that are important in the formation of the social, moral, intellectual and emotional education of students. Effective methods of assessing educational abilities, the importance of developing students individually and in groups are indicated. The article provides the necessary methodological tools for taking into account psychological and pedagogical factors in assessing educational abilities, as well as for organizing the goal-oriented activities of students. It is also emphasized that the interaction of teachers, parents and society is important in the development of educational abilities of students. This article is useful as a practical guide to the effective assessment and development of educational abilities of students.